Sequential Systemic Administrations of Combretastatin A4 Phosphate and Radioiodinated Hypericin Exert Synergistic Targeted Theranostic Effects with Prolonged Survival on SCID Mice Carrying Bifocal Tumor Xenografts - Li, Junjie (Ivyspring International Publisher, 2013)
Objectives: Based on the soil-to-seeds principle, we explored the small-molecular sequential dual-targeting theranostic strategy (SMSDTTS) for prolonged survival and imaging detectability in a xenograft tumor model. Materials and Methods: Thirty severe combined immunodeficiency (SCID) mice bearing bilateral radiation-induced fibrosarcoma-1 (RIF-1) subcutaneously were divided into group A of SMSDTTS with sequential intravenous injections of combretastatin A4 phosphate (CA4P) and (131)I-iodohypericin ((131)I-Hyp) at a 24 h interval; group B of single targeting control with CA4P and vehicle of (131)I-Hyp; and group C of vehicle control (10 mice per group). Tumoricidal events were monitored by in vivo magnetic resonance imaging (MRI) and planar gamma scintiscan, and validated by ex vivo autoradiography and histopathology. Besides, 9 mice received sequential intravenous injections of CA4P and (131)I-Hyp were subjected to biodistribution analysis at 24, 72 and 120 h. Results: Gamma counting revealed fast clearance of (131)I-Hyp from normal organs but intense accumulation in necrotic tumor over 120 h. After only one treatment, significantly prolonged survival (p<0.001) was found in group A compared to group B and C with median survival of 33, 22, and 21 days respectively. Tumor volume on day 15 was 2.0 ± 0.89, 5.66 ± 1.66, and 5.02 ± 1.0 cm(3) with tumor doubling time 7.8 ± 2.8, 4.4 ± 0.67, and 4.5 ± 0.5 days respectively. SMSDTTS treated tumors were visualized as hot spots on gamma scintiscans, and necrosis over tumor ratio remained consistently high on MRI, autoradiography and histology. Conclusion: The synergistic antitumor effects, multifocal targetability, simultaneous theranostic property, and good tolerance of the SMSDTTS were evident in this experiment, which warrants further development for preclinical and clinical applications.